Natural enemies depend on remnant habitat size in agricultural landscapes - Jordani, Mainara Xavier [UNESP]; Hasui, Erica; Silva, Vinicius Xavier da (Northeast Forestry Univ, 2015)
In recent decades, the consequences of habitat fragmentation have been of growing concern, because it is particularly important to understand how fragmentation may affect biodiversity, an ecological service. We tested two hypotheses: (1) that natural fragment size in agricultural landscapes indirectly affects the herbivore through effects on natural predator populations; and (2) predator activity into the crop reduces along the distance from the natural fragment edge. From 2008 and 2009, we conducted our study in seven forest remnants and in surrounding coffee plantations (fragments ranged from 6 to 105 ha, mean 49.28 +/- A 36.60 ha) in Southern Minas Gerais, Brazil. Birds were sampled by point counts, and insect predation was evaluated by using an artificial insect model (Koh and Menge 2006). Our results suggest that although there were many potential predators (e.g., wasps, ants, birds, and mammals), birds were the most important taxon unit. The covariance analysis supported the hypothesis that patch size affected the number of larvae predation by overall taxi, but there was no support for a distance effect. These findings suggest that natural enemies'ecological service (mainly from birds) declined with remnant reduction, which has implications not only for human welfare, but also in strengthening the economic justifications for conserving the remaining natural habitats and biodiversity in agricultural landscapes.
Keywords: Ecosystem service; Fragmentation; Isolation; Insectivore; Predation